Pengaruh Innovative Work Behavior, Competency dan Teamwork terhadap Kinerja Karyawan di CV. Faris Collection Sidoarjo - Wulan Fitri Yanti; Sumartik; Hasan Ubaidillah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to determine the influence of innovative work behavior, competency and teamwork on employee performance. This study uses a quantitative approach. The population in this study were all employees at CV. Faris Collection Sidoarjo, totaling 104 employees, were used as respondents using saturated sampling techniques. The independent variables are innovative work behavior, competency and teamwork, while the dependent variable is employee performance. The data collection technique uses a questionnaire with Likert scale measurements. The data analysis technique uses SPSS version 25 software. Based on the research results and discussions that have been described, it can be concluded that there is a positive and significant influence between innovative work behavior, competency and teamwork variables on employee performance. Each variable also indicates that there is a positive and significant influence. Where the variable innovative work behavior has a partial and simultaneous effect on employee performance, competency has a partial and simultaneous effect on employee performance, and teamwork also has a partial and simultaneous effect on employee performance